Relative efficiency of anuran sampling methods in a restinga habitat (Jurubatiba, Rio de Janeiro, Brazil) - C. F. D. Rocha; M. Van Sluys; F. H. Hatano; L. Boquimpani-Freitas; R. V. Marra; R. V. Marques (Brazilian Journal of Biology)
Studies on anurans in restinga habitats are few and, as a result, there is little information on which methods are more efficient for sampling them in this environment. Ten methods are usually used for sampling anuran communities in tropical and sub-tropical areas. In this study we evaluate which methods are more appropriate for this purpose in the restinga environment of Parque Nacional da Restinga de Jurubatiba. We analyzed six methods among those usually used for anuran samplings. For each method, we recorded the total amount of time spent (in min.), the number of researchers involved, and the number of species captured. We calculated a capture efficiency index (time necessary for a researcher to capture an individual frog) in order to make comparable the data obtained. Of the methods analyzed, the species inventory (9.7 min/searcher /ind.- MSI; richness = 6; abundance = 23) and the breeding site survey (9.5 MSI; richness = 4; abundance = 22) were the most efficient. The visual encounter inventory (45.0 MSI) and patch sampling (65.0 MSI) methods were of comparatively lower efficiency restinga, whereas the plot sampling and the pit-fall traps with drift-fence methods resulted in no frog capture. We conclude that there is a considerable difference in efficiency of methods used in the restinga environment and that the complete species inventory method is highly efficient for sampling frogs in the restinga studied and may be so in other restinga environments. Methods that are usually efficient in forested areas seem to be of little value in open restinga habitats.